Divergent gut microbial metabolism supports niche partitioning in giant and red pandas - Zhou, Yanshan; Qi, Dunwu; Chen, Chao; Bi, Wenlei; Yu, Xiang; Liu, Jiabin; Lan, Guanwei; Hou, Rong; Li, Zusheng; Ma, Rui (Frontiers in Microbiology, 2025)
IntroductionThe gut microbiota plays a pivotal role in regulating the host's physiological functions and behavior. The coevolutionary relationship between the host and its gut microbiota facilitates adaptation to specific ecological niches. As obligate bamboo feeders, giant pandas (Ailuropoda melanoleuca) and red pandas (Ailurus styani) exhibit distinct feeding preferences: the former primarily consumes bamboo stems and leaves, while the latter feeds mainly on bamboo leaves. This study aims to elucidate how these species adapt metabolically to different parts of bamboo via gut microbial activity.MethodsWe employed 16S rRNA gene sequencing to analyze the structure and function of fecal microbial communities in giant pandas (GP) and red pandas (RP).ResultsSignificant differences in gut microbiota composition were observed between the GP and RP groups. Eight core bacterial taxa constituted over 99.97% of the total microbial composition, with the RP group exhibiting higher species richness but lower overall diversity. At the phylum level, Proteobacteria, Bacteroidetes, Actinobacteria, Acidobacteria, and Flavobacteria were significantly enriched in the GP group, whereas Firmicutes dominated in the RP group. At the genus level, Sphingomonas, Methylobacterium, Cryomonas, and Terriglobus were more abundant in the GP group, while Streptococcus and Rhizobium were enriched in the RP group. Functional metabolic analysis indicated that lipid and amino acid metabolism pathways were significantly enriched in the GP group, whereas nucleotide and carbohydrate metabolism pathways were prominent in the RP group. Further analysis revealed that Sphingomonas and Methylobacterium in the GP group positively regulated amino acid and lipid metabolism, while Streptococcus in the RP group enhanced nucleotide and carbohydrate metabolism.DiscussionThese findings suggest that the distinct metabolic pathways of the gut microbiota in giant and red pandas have evolved in concert with their dietary strategies, energy acquisition modes, and ecological niche differentiation, forming a highly coordinated adaptive system.